Managing Sustainable Tourism in Monkey Forest Ubud due to Covid-19 Pandemic - Sudira, I Putu; Mudana, I Gede (Bali Membangun Bali: Jurnal Bappeda Litbang, 2021)
Purpose: This study aims to determine the sustainable tourism management of Monkey Forest Ubud, Bali, Indonesia, in the presence of the Covid-19 pandemic which has resulted in a tourism crisis. Research methods: This study uses a qualitative method to describe the condition of Monkey Forest Ubud in the presence of the Covid-19 pandemic. It is explained in a descriptive manner to show the sustainability management applied by its management during the pandemic. Results and discussion: The management of Monkey Forest Ubud carries out operations by paying attention to economic, ecological and socio-cultural aspects, which aims to create sustainable tourism in the pandemic situation, so as to create harmonization of relations between the surrounding community and the manager of such an attraction. Implication: The management must pay attention to economic, ecological and socio-cultural aspects which shows that Monkey Forest Ubud supports sustainable tourism.